Learning Semantic Representations for the Phrase Translation Model - Gao, Jianfeng; He, Xiaodong; Yih, Scott Wen-tau; Deng, Li (2013)
This paper presents a novel semantic-based phrase translation model. A pair of source and target phrases are projected into continuous-valued vector representations in a low-dimensional latent semantic space, where their translation score is computed by the distance between the pair in this new space. The projection is performed by a multi-layer neural net-work whose weights are learned on parallel training data. The learning is aimed to directly optimize the quality of end-to-end machine translation results. Experimental evaluation has been performed on two Europarl translation tasks, English-French and German-English. The results show that the new semantic-based phrase translation model significantly improves the performance of a state-of-the-art phrase-based statistical machine translation system, leading to a gain of 0.7-1.0 BLEU points.